International student recruitment in policy and practice: A research from Turkey - DEVRIM VURAL YILMAZ (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This research aims to make projections about the efforts. Turkish universities are making to attract international students. Some nations like Turkey are actively trying to attract more foreign workers. Managers of international student offices are the focus of the research because they are both policymakers and practitioners and, as a result, have unique perspectives on international recruitment.Methodology: Data were collected from the International Office Directors of Turkish universities via a survey conducted between December 2014 and February 2016. The online survey tool Survey Monkey was used to collect responses.Findings: According to the research conducted, international student offices in Turkish universities are relatively new establishments that lack authority and personnel. In addition, the board members all agreed that universities do not provide enough funding for international outreach. Similarly, many higher education institutions do not systematically plan for international students.Implications/Novelty: There are still significant obstacles that must be carefully addressed before Turkish universities can truly reap the benefits of their increased international student enrollment. Insights into how to solve these issues have been provided by this study, which has brought to light the issues that international students face.